The Influence of Product Quality and Word of Mouth on Repurchase Intention with Purchase Decision as a Mediating Variable in the Use of Online Transportation - Asmarani Pandabandjal; Arini Hidayah; Wida Purwidianti; Irawan Randikaparsa (Dinasti Publisher, 2025)
This study aims to analyze the influence of product quality and word of mouth on repurchase intention, with purchase decision as a mediating variable among users of Gojek services. This research adopts a quantitative approach through a survey of active Gojek users. The population in this study consists of all Gojek service users in Indonesia. The sample was determined using the Lemeshow formula, resulting in a total of 200 respondents. Data were analyzed using the Structural Equation Modeling (SEM) method. The results indicate that product quality and word of mouth have a positive effect on purchase decision and repurchase intention. Furthermore, purchase decision significantly mediates the relationship between product quality and word of mouth on repurchase intention. These findings highlight the importance of improving service quality and encouraging positive word of mouth to build